Junior Senior Farewell - Unknown:::Creator::::::::::::
Photograph shows the Junior Senior Farewell held on June 23, 1914 in the Quad at San Jose State Normal School. In this picture, students are lined up in rows and standing with their arms outstretched to their sides. Some students have extra panels of sheer fabric that they are holding in their hands.